CORRECTION OF FACIAL ASYMMETRY OF THE UPPER THIRD OF THE FACE: CASE REPORT - Almeida, Victória Lourenne Silva; de Sousa Carvalho Reis, Mauricio; Nogueira, Luciana Tolstenko; Nogueira, Ludmila Tolstenko; Lopes Neto, Raimundo Nonato Santos (Editora Impacto Científico, 2025)
Facial and body aesthetic procedures are becoming increasingly popular due to the pursuit of symmetry and perfection. In this context, botulinum toxin (BTX) has emerged as an effective option for facial rejuvenation and harmonization. Its mechanism of action involves promoting flaccid and transient neuromuscular paralysis through chemical denervation. The objective of this study was to report a clinical case of a patient with facial asymmetry in the upper third of the face, describing its identification, diagnosis, and treatment. Methods: This is a descriptive case report developed at a teaching clinic specializing in Orofacial Harmonization. An alternative treatment using botulinum toxin type A was proposed. After its application, physical benefits, including improved muscle strength and endurance, as well as psychological benefits, were observed, providing improved quality of life, self-esteem, and overall well-being. The study concluded that, as a non-invasive and reversible method, it is a viable alternative for similar cases. DOI: 10.56238/edimpacto2025.060-005